Acoustic startle and prepulse inhibition predict smoking lapse in posttraumatic stress disorder. (October 2015) - Vrana, Scott R; Calhoun, Patrick S; Dennis, Michelle F; Kirby, Angela C; Beckham, Jean C
Most smokers who attempt to quit lapse within the first week and are ultimately unsuccessful in their quit attempt. Nicotine withdrawal exacerbates cognitive and attentional problems and may be one factor in smoking relapse. The startle reflex response and prepulse inhibition (PPI) of the response are sensitive to arousal and early attentional dysregulation. The current study examined whether startle response and PPI are related to early smoking lapse, and if this differs in people with and without posttraumatic stress disorder (PTSD). Participants with ( N = 34) and without ( N = 57) PTSD completed a startle reflex and PPI assessment during (1) ad lib smoking (2) on the first day of abstinence during a quit attempt. Most (88%) participants lapsed within the first week of the quit attempt. PTSD status predicted shorter time to lapse. Larger startle magnitude and greater PPI predicted a longer duration before smoking lapse. When diagnostic groups were examined separately, greater PPI predicted a longer successful quit attempt only in participants with a PTSD diagnosis. The startle reflex response and PPI may provide an objective, neurophysiological evaluation of regulation of arousal and early attentional processes by nicotine, which are important factors in smoking cessation success.